Parallel Model for Vocational Teachers Training - Adamonienė, Rima (Acta Paedagogica Vilnensia, 2003)
Parallel training of vocational teachers includes acquiring a profession together with the modulus of pedagogy and psychology at a university of a certain professional direction in which there is a department of Professional Pedagogy and Psychology. In this way professional consciousness develops, insuring new quality of individuality expression, while performing professional teaching activity where professionally important values and individual stereotypes develop. Parallel training allows remaining flexible in satisfying the needs of schools for preparation of teachers of needed professions and education does not demand additional expenses, because already admitted students (starting from the third year) choose their area of majoring. In the third year the students develop their majoring ideas either influenced by demand or wish therefore they have a motivated understanding of their personality and profession relationship. A rule using this method of training in the final stage of studies the highest training results are achieved. Only university research allows a broad understanding and adequate selection of the professional education content for professional training at each purpose school. Therefore vocational teachers cannot be trained at schools or colleges. Teachers of each kind of profession should he educated al the universities of different professional direction, providing them with a possibility to acquire higher and higher professional and pedagogy qualification. Teachers of profession cannot be educated at the universities, which are not related to any professional direction. Since students in the system of professional education are less intellectual and the period of adolescence and young adult life is more conflicting, the vocational teacher should possess a systematic pedagogic preparation.
Keywords: higher education; teacher education; vocational teachers; parallel model; students